MODEL INTERAKSI SOSIAL DALAM MENGELABORASI KETERAMPILAN SOSIAL - Muhammad Mushfi El Iq Bali (PEDAGOGIK : JURNAL PENDIDIKAN, 2017)
The main role of education is to prepare citizens who can develop integrated democratic behavior, both in the private and social order that enhance the productive social democratic life. Therefore, the learning process should be a vehicle to prepare learners in order to interact widely with the community, develop democratic attitudes and behaviors, and foster the productivity of learning activities of learners. This can be applied by applying a model of social interaction, so learners can interact well and improve social skills in the community as mandated by national law and education objectives. Meanwhile, self-development is needed in the actualization of individuals in the environment around the learner. Actualization of individuals in the self-development of students can be developed through active learning and develop social skills, so as to lead students to have a better mental. In addition, students have better emotional health by developing their self-confidence and realistic feelings in instilling empathy for others. Collaborative learning models of social interaction provide solutions to optimize social skills in response to social gaps and social behavior attitudes of learners as well as social symptoms and problems in today's society.